The Association between Intraocular Pressure and Predictors of Coronary Heart Disease Risk in Koreans - Lee, Yong-Wha (The Korean Academy of Medical Sciences, 2008)
Elevated intraocular pressure (IOP) is one of the major risk factors for glaucomatous visual field defects. Each individual systemic risk factor of coronary heart disease (CHD) is associated with elevated IOP, although no reports have argued for a correlation between the risk factors for CHD and IOP after a comprehensive or collective analysis. The National Cholesterol Education Program Adult Treatment Panel III presented the Framingham projection, which can predict the risk of CHD quantitatively. We investigated the association between IOP and the Framingham projection in 16,383 Korean subjects. The Framingham projection was applied using the indicated risk factors. The associations between the Framingham projection and IOP and the influences of the risk factors on the IOP were examined. The Framingham projection was correlated with the mean IOP in women (p<0.05). The relationship between IOP and systemic variables other than smoking was significant (p<0.05). The mean IOP was significantly higher in the high-risk CHD group than in the low-risk group based on the Framingham projection (p<0.05). Because an elevated IOP was associated with cardiovascular risk factors, subjects with a high CHD risk based on the Framingham projection need continuous monitoring for IOP to prevent glaucomatous visual field defects.